Gender wise Comparative Study on the Prevalence of Neck Pain among Dentist in Single Dental Treatment - V. , Swaminathan; P. , Sankaralingam; S. , Subbiah M.P.T (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To ascertain common gender in dental professionals for prevalence of developing neck pain in a single dental procedure.Setting and Participants: The dental professionals have private clinics and dental hospitals. Sixty samples were selected, and among these, thirty numbers are grouped in each gender.Outcome Measure: The numerical pain rating scale was used in this study.Result: Both genders developed pain in their necks during a single dental treatment application. But the intensity of pain discrepancy is seen in both genders. Conclusion: From the results, both genders of dentists elicit neck pain during their treatment of the patients. So better they can have ergonomics and neck exercises for prevention of neck pain developing.